Formy adresatywne w powieści "Wdowiec" Józefa Korzeniowskiego = Addressative forms in the novel "The Widower" by Jozef Korzeniowski - Żurawska-Chaszczewska, Jowita (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The goal of the article is the analysis of linguistic etiquette exponents which are associated with addressative forms in "The Widower" by Jozef Korzeniowski. The text mentions addressative forms including first names, surnames, relativity terms, official titles, old-Polish addressative forms and analyses the application of expressions such as Mr, Mrs, and Ms, or addressative forms directed to specific groups such as clergymen, etc.
Keywords: stylistyka; język pisarzy; grzeczność językowa; style; writer`s, language; linguistic politeness